Changes in Soil Microbial Activity, Bacterial Community Composition and Function in a Long-Term Continuous Soybean Cropping System After Corn Insertion and Fertilization - Rao, Demin; Meng, Fangang; Yan, Xiaoyan; Zhang, Minghao; Yao, Xingdong; Kim, Kyung Seok; Zhao, Jing; Qiu, Qiang; Xie, Futi; Zhang, Wei (Frontiers in Microbiology, 2021)
Corn-soybean rotation and fertilization are common practices improving soil fertility and crop yield. Their effects on bacterial community have been extensively studied, yet, few comprehensive studies about the microbial activity, bacterial community and functional groups in a long-term continuous soybean cropping system after corn insertion and fertilization. The effects of corn insertions (Sm: no corn insertion, CS: 3 cycles of corn-soybean rotations and CCS: 2 cycles of corn-corn-soybean rotations) with two fertilization regimes (No fertilization and NPK) on bacterial community and microbial activity were investigated in a long-term field experiment. The bacterial communities among treatments were evaluated using high-throughput sequencing then bacterial functions were predicted based on the FaProTax database. Soil respiration and extracellular enzyme activities were used to assess soil microbial activity. Soil bacterial community structure was significantly altered by corn insertions (p<0.01) and fertilization (p<0.01), whereas bacterial functional structure was only affected by corn insertion (p<0.01). The activities of four enzymes (Invertase, β-glucosidase, β-xylosidase and β-D-1,4-cellobiohydrolase) involved in soil C cycling were enhanced by NPK fertilizer, and were also enhanced by corn insertions except for the invertase and β-xylosidase under NPK fertilization. NPK fertilizer significantly improved soil microbial activity except for soil metabolic quotient (qCO2) and the microbial quotient under corn insertions. Corn insertions also significantly improved soil microbial activity except for the ratio of soil induced respiration (SIR) to basal respiration (BR) under fertilization and the metabolic quotient (qCO2) was decreased by corn insertions. These activity parameters were highly correlated with the soil functional capability of aromatic compound degradation， which was the main predictors of bacterial functional structure. In general, the combination of soil microbial activity, bacterial community and corresponding functional analysis provided comprehensive insights into compositional and functional adaptations to corn insertions and fertilization.